Optimalisasi Pengetahuan dan Dukungan Keluarga Pada Keluarga Pasien Hipertensi Terhadap Pengendalian Hipertensi Di Desa Sarampad Kec. Cugenang: Optimalisasi Pengetahuan dan Dukungan Keluarga Pada Keluarga Pasien Hipertensi Terhadap Pengendalian Hipertensi Di Desa Sarampad Kec. Cugenang - Ayu, Shinta Arini; Novryanthi, Dhinny; Yulendasari, Rika; Nurhamdan Arif, Idan; Aulia Rahayu, Adiah (Ruang Ide Publisher, 2023)
Last November 2022, Cianjur Regency was hit by an earthquake which left deep wounds. Not only causing fatalities, missing people, minor and serious injuries, damage to residential buildings, infrastructure and other public facilities was also badly damaged. Not only that, the post-disaster impact that emerged was on ongoing problem that arose at the evacuation post (tent), namely the emergence of several diseases, one of which was a problem, comorbid disease (hypertension). One of the actions to reduce the incidence of hypertension is to increase knowledge and support of the patient’s family. The purpose of this activity is to increase the knowledge, especially to the family of hypertensive patients whose and result can provide adequate support for controlling reccurence in hypertensive patients. The method used is directing counseling through media, leafleats and flipcharts as well as evaluation in the form of pre and post tests. The results obtained showed that of the 107 participants who received counseling, the participants’ knowledge increased, participants with the good knowledge were 56 (52.33%), participants with sufficient knowledge incrased to 34 (31,77%) and participants with less knowledge decreased to 17 (15.89%) participants. Therefore health education must be carried out regularly within a certain period of time, of course not only knowledge needs to be increased but social support from the family greatly influences hypertensive patients to control their disease.